Analisis Keberlanjutan Aspek Sosial Ekonomi Pada Kampung Topeng, Tlogowaru di Kota Malang Pasca Pandemi Covid-19 - Pratiwi, Magvira Ardhia; Giriwati, Novi Sunu Sri (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 9 No 2 (2022): October 2022DO - 10.24843/JRS.2022.v09.i02.p02, 2022)
The vast and rapid viral spread during the Covid-19 pandemic in Indonesia urged the government to impose a Large-Scale Social Restriction Regulation. One significant impact of this restriction is the closure of vast tourist destinations, including Kampung Topeng, in the Tlogowaru District of Malang City. The development of this kampung into a tourist destination is one of the Desaku Menanti Program’s initiatives, which aims at improving the living standard of the homes-less members of the community by providing them with opportunities to work within their kampung which has been now developed into a tourist destination. It had headed toward achieving this objective till the Covid-19 pandemic arrived at the end of 2019. Tourism-related activities have stopped, and so has its economic contribution. Focusing its discussion on the socio-economic issues, this study examines the development practices at the Kampung Topeng in the aftermath of the Covid-19 pandemic. It bases its analysis on indicators outlined by the Sustainable Development Goals (SDGs). The study implemented a qualitative descriptive method in which data were obtained from observations and interviews with relevant stakeholders and residents. Overall, the study result shows that Kampung Topeng tourist development is unsustainable. Having examined how each SDGs is reflected in development practices, this study finds that three SDGs are accommodated in a ‘sustainable’ manner, two SDGs are reflected in a ‘quite sustainable’ ways, and six SDGs are embedded in an ‘unsustainable’ degree. It is expected that these review results will assist relevant local governments in instigating a guideline for socio-economically sustainable tourism; thus, its goal to halt the return of the homeless group to the street and enhance its welfare is achievable. Keywords: village tourism; social, economy; SDGs, post Covid-19   Abstrak Persebaran virus secara luas dan cepat di masa pandemi Covid-19 di Indonesia memicu pemberlakuan Peraturan Pembatasan Sosial Berskala Besar. Salah satu dampak dari pembatasan ini adalah penutupan tempat wisata, seperti halnya yang terjadi di Kampung Topeng, Kelurahan Tlogowaru di Kota Malang. Pembangunan Kampung ini sebagai destinasi wisata merupakan salah satu inisiatif dari Program Desaku Menanti yang bertujuan meningkatkan taraf hidup para gelandangan dengan membuka kesempatan kerja di kampungnya sendiri yang sekarang telah dibangun sebagai destinasi wisata. Pada awalnya usaha ini sudah mengarah pada pencapaian tujuan sampai tibanya pandemi Covid-19 di akhir tahun 2019. Kegiatan kepariwisataan terhenti, begitu pula halnya dengan kontribusi ekonomi. Dengan memfokuskan kajian pada aspek sosial-ekonomi, penelitian ini mengkaji beragam praktek pembangunan di Kampung Topeng pasca pandemi Covid-19. Analisa dalam studi ini didasari oleh indikator-indikator yang ditetapkan dalam Sustainable Development Goals (SDGs). Studi ini menerapkan metode deskriptif kualitatif. Data didapatkan dari observasi dan wawancara dengan stakeholder dan warga. Hasil studi menunjukkan bahwa pembangunan di Kampung Topeng belum berkelanjutan. Dengan mengkaji sejauh mana SDGs direfleksikan dalam praktek pembangunan, penelitian ini menemukan jika tiga item SDGs sudah diakomodasi pada level ‘berkelanjutan,’ dua SDGs direfleksikan dalam kategori ‘cukup berkelanjutan,’ dan enam SDGs dirangkul pada klasifikasi ‘belum berkelanjutan.’ Diharapkan jika temuan ini akan menjadi acuan dalam penyusunan panduan pembangunan industri wisata yang secara sosial ekonomi berkelanjutan, sehingga upaya menstop kembalinya para gelandangan ke jalan, dan peningkatan kesejahteraannya bisa tercapai. Kata kunci: kampung wisata; sosial; ekonomi; SDGs; pasca Covid-19